Amniocentesis in the HIV-Infected Pregnant Woman: Is There Still Cause for Concern in the Era of Combination Antiretroviral Therapy? - Nisha Andany; Michelle Letchumanan; Lise Bondy; Kellie Murphy; Mona R Loutfy (Canadian Journal of Infectious Diseases and Medical Microbiology)
The current standard of care in Canadian obstetrical practice is to offer pregnant women the opportunity for prenatal investigation to diagnose congenital abnormalities. Prenatal amniocentesis is Canada’s most commonly practiced invasive procedure for the diagnosis of chromosomal and single gene disorders. The potential risk of intrapartum HIV transmission during amniocentesis raises several ethical concerns and limits the availability of prenatal genetic testing for HIV-positive pregnant women. Complete virological suppression with antiretroviral therapy may alleviate the risk of mother-to-child transmission during amniocentesis and increase accessibility of this important diagnostic tool in the HIV-positive population. The present report describes a case involving a 32-year-old HIV-positive pregnant woman whose plasma viral load was undetectable on antiretroviral therapy; she underwent successful prenatal amniocentesis without transmission of HIV to her infant.